ANALYZING AIRLINE DELAY PROPAGATION AND DELAY CAUSE USING A GAUSSIAN NETWORK - Kwon, Yeongjun; Zhang, Ruiyou; Moon, Ilkyeong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
We developed a delay propagation model for an airline network using a Gaussian network approach. By analyzing US flight data in a case study, we evaluated the effects of delay propagation within an airline network. The model has several advantages, such as accounting for non-independent and identically distributed delay profiles, providing a more accurate representation of the observed delay propagation process, and identifying weak links in an airline network. Various scenario studies of delay propagation revealed that the Gaussian network model could capture the effect of delay propagation more precisely than previous studies. Moreover, the Gaussian network model could identify weak links through a statistical approach in an airline network. These perspectives may be valuable in developing approaches for managing the delay propagation and alleviating its subsequent effect.